Temporal, spatial and demographic distributions characteristics of COVID-19 symptom clusters from chinese medicine perspective: a systematic cross-sectional study in China from 2019 to 2023 - Bin Liu; Tian Song; Mingzhi Hu; Zhaoyuan Gong; Qianzi Che; Jing Guo; Lin Chen; Haili Zhang; Huizhi Li; Ning Liang; Jing Wan; Kunfeng Wang; et al. (Chinese Medicine)
Abstract Background The subtypes diagnosis of disease symptom clusters, grounded in the theory of “Treatment in Accordance with Three Categories of Etiologic Factors” and International Classification of Diseases 11th Revision (ICD-11), is a vital strategy for Chinese Medicine (CM) in treating unknown respiratory infectious diseases. However, the classification of disease symptom clusters continues to depend on empirical observations and lacks robust scientific evidence. Consequently, this study seeks to explore the temporal, spatial and demographic distributions characteristics of Corona Virus Disease 2019 (COVID-19) symptom clusters in China. Methods PubMed, Web of Science, Science direct, WHO, Litcovid, CNKI databases were searched from inception until December 31, 2023. Optical character recognition technology and image recognition technology were employed to identify tables within the papers. Four researchers independently screened and extracted data, resolving conflicts through discussion. Heat mapping and hierarchical clustering techniques were utilized to analyze COVID-19 symptom clusters. Data analysis and visualization were conducted using R software (4.2.0), while the association analysis of symptom clusters was performed using Cytoscape (3.10.2). Results A total of 366 COVID-19 clinical trials with 86,972 cases including 66 clinical symptoms of 7 disease systems and other clinical manifestations in China were included. In temporal distribution, 63 symptoms centered around fatigue and 44 symptoms focused on chest tightness are characteristic of symptom clusters in spring and winter, respectively. With the addition of spatial distribution, the symptom clusters in middle and low latitudes during spring are characterized by 53 symptoms centered around fatigue and cough, and 51 symptoms focused on fatigue, respectively. During winter, the symptom clusters in middle and low latitudes are characterized by 38 symptoms centered around chest tightness and 37 symptoms focused on fever, respectively. When considering demographic distribution, the symptom clusters for < 50 years are characterized by fatigue as the core symptom in middle (44 symptoms)/low (28 symptoms) latitudes during spring and middle latitude (25 symptoms) during winter. For ≥ 50 years, the symptom clusters in middle latitude (49 symptoms) during spring and low latitudes (35 symptoms) during winter are centered around cough, while in low latitude (27 symptoms) focuses on diarrhea during spring, and middle latitude (35 symptoms) emphasizes both diarrhea and chest tightness during winter. Conclusion In summary, variations in symptom clusters and core symptoms of COVID-19 in temporal, spatial and demographic distributions in China offer a scientific rationale for the “Treatment in Accordance with Three Categories of Etiologic Factors” theory. These interesting findings prompt further investigation into CM patterns in the ICD-11, and suggest potential strategies for personalized precision treatment of COVID-19. High-quality clinical studies focusing on individual symptoms are warranted to enhance understanding of respiratory infectious diseases.